Effect of dangke administration on serum TNF-a and liver SOD levels in rats induced by a high-fat, high-sugar diet - Uzifatun Nur Y.F Lapatta; Diana Nur Afifah; Ardiyan Pramono; Ninik Rustanti (AcTion: Aceh Nutrition Journal, 2024)
Dangkes contain lactic acid bacteria that improve obesity by controlling the intestinal flora, improving the micro-ecological balance in the gut, and boosting the immune system. This study aimed to analyze the differences in serum TNF-α and liver SOD levels in obese rats fed a Dangke diet. The research was conducted from December to January 2024 at the PSPG PAU UGM using a true-experiment design post-test with only the control group. Male Sprague-Dawley rats (n=30) were randomly divided into five groups: healthy rats (KS), obese rats given standard feeding (K-), obese rats received L-Bio (K+), obese rats were given Dangke at a low dose (P1), and obese rats received Dangke at a high dose (P2). Intervention for 28 days. Data analysis was performed using one-way ANOVA tests and further post-hoc Bonferroni tests.  The result obtainded that Dangke with dose dose of 3,6 g/200 gBB was effective in decreasing TNF-α levels and increasing SOD levels (p<0,05). P2 had the lowest mean TNF-α level (7,33 ± 0,22) compared to K+ (8,59 ± 0,22) and P1 (8,88 ± 0,18). P2 had the highest SOD levels compared to K+ (62,56 ± 4,06) and P1 (61,47 ± 4,71).  In conclusion, Dangke effectively overcame inflammation and oxidative stress in obesity.